Electrochemical ammonia synthesis via nitrate reduction on perovskite LaxFeO3−δ with enhanced efficiency by oxygen vacancy engineering. Issue 20 (21st September 2022) - Yin, Qi; Hu, Shihao; Liu, Jingwen; Zhou, Hao
Abstract : The oxygen vacancy-rich perovskite La0.9 FeO3− δ was employed as an electrocatalyst to reduce nitrate to ammonia and obtained the highest NH3 yield of 1024.8 μg h −1 cm −2 at −1.0 V ( vs. RHE) and a faradaic efficiency of 78.1% at −0.8 V ( vs. RHE). Abstract : It is a novel and challenging task to seek an effective electrocatalyst to synthesize valuable ammonia from the harmful nitrate in the wastewater. This work innovatively applied the perovskite La x FeO3− δ ( x = 1, 0.95, 0.9) as an electrocatalyst to reduce nitrate to ammonia. For the catalyst L0.9 F, the highest NH3 yield was up to 1024.8 μg h −1 cm −2 at −1.0 V ( vs. RHE), while the maximum faradaic efficiency was 78.1% achieved at −0.8 V ( vs. RHE). The outstanding electrocatalytic activities were attributed to the oxygen vacancies generated from the A-site deficiencies. The N–O bonds were weakened with the oxygen atoms in the nitrate filling the oxygen vacancies. The adsorption and transformation of reaction intermediates were promoted due to the existence of oxygen vacancies. Meanwhile, the oxygen vacancies could serve as the active sites of the catalysts, and the deficiencies enhanced the charge transfer efficiency. This work provides a direction to fabricate efficient electrocatalysts for reducing nitrate to ammonia, which can effectively assist in handling both the energy crisis and the environmental pollution.